Wobec przemijania: Jegor Bułyczow i inni Maksyma Gorkiego – próba (re)intepretacji .......... 523 - Krycka-Michnowska, Iwona (Czas w kulturze rosyjskiej, 2019)
IN THE FACE OF TRANSIENCE. MAXIM GORKY’S YEGOR BULYCHOV AND OTHERS. THE ATTEMPT AT (RE)INTERPRETATIONThe topic of this paper is the Maxim Gorky’s play Yegor Bulychov and Others. It was one of the most often exhibited plays of this author in Poland, both in the interwar period and after the war. The interpretations of Gorky’s work were similar in People’s Poland to those in Soviet Russia, consistent with the assumptions of socialist realism. The paper recalls the genesis of the play and presents an analysis that exposes its universal meaning. It was interpreted primarily as a play that pertains to philosophical and ethical issues, raises questions about the meaning of life and ars moriendi; as a work which concerns the theme of a spiritual awakening or an existential transformation of a man who realizes his loneliness and emptiness of his own life just before his death.